Effects of Selenium on Some Reproductive Parameters in Acrylamide- Induced Testis Toxicity in Rats - YILDIRIM, SERKAN; Sengul, Emin; Aksu, Emrah Hicazi; Cinar, İrfan; Gelen, Volkan; Tekin, Samet; Dag, Yusuf (Springer Science and Business Media LLC, 2022)
Abstract
In this study, the effects of Selenium (Se) in testis toxicity induced by Acrylamide (ACR) in rats were investigated. In our study, 50 male adult rats were used and the rats were divided into 5 groups; Control, ACR, Se0.5 + ACR, Se1 + ACR, and Se1. Se and ACR treatments were applied to the rats for 10 days. On the 11th day of the experimental study, intracardiac blood samples from the rats were taken under anesthesia and decapitated. Sperm motility and morphology were evaluated. Dihydrotestosterone, FSH, and LH levels in sera were analyzed with commercial ELISA kits. MDA, SOD, GSH, GPx, CAT, TNF-α, IL-6, and IL-1β levels in testicular tissues were analyzed by commercial ELISA kits. Expression analysis of HSD17B1, StAR, CYP17A1, MAPk14, and P-53 as target genes was performed with Real Time-PCR System technology for each cDNA sample synthesized from rat testis RNA. Testicular tissues were evaluated by histopathological, immunohistochemical, and immunofluorescent examinations. Serum dihydrotestosterone and FSH levels significantly decreased in the ACR group compared to the control group, while LH levels increased. A high dose of Se prevented these changes caused by ACR. ACR induced testicular oxidative stress, inflammation, apoptosis, changes in the expression of reproductive enzymes, some changes in sperm motility and morphology, DNA, and tissue damage, and Se administration prevented these changes caused by ACR. As a result of this study, it was determined that Se prevents oxidative stress, inflammation, apoptosis, and DNA damage in testicular toxicity induced by ACR in rats.
Keywords: 3. Good health